Preparation of the electrospun polyvinylidene fluoride / polyvinyl alcohol scaffold as a potential tissue replacement - Hamzah, Mohd Syahir Anwar; Ab Razak, Nurul Amira; Ng, Celine; Abdul Azize, Akmal Hafiszi; Abdul Sukor, Jumadi; Soon, Chin Fhong; Idris, Mohd Safiee; Mat Nayan, Nadirul Hasraf (IIUM Press, 2020)
Polyvinylidene fluoride (PVDF), a piezoelectric material, is commonly used in tissue engineering due to its potential for mimicking the electrical microenvironment of biological conditions for tissue development. In this present research, polyvinyl alcohol (PVA) was introduced into electrospun PVDF fabrication through an electrospinning process, aiming to enhance the nanofibrous membrane's biocompatibility properties by improving the hydrophilicity properties to act as an artificial tissue scaffold. The electrospun PVDF/PVA membranes are found to be optimum at a PVDF-to-PVA ratio of 90:10 due to its excellent mechanical, morphological, and hydrophilicity conductivity properties. Fourier transform infrared (FTIR) spectroscopy verified strong hydrogen bonding interaction formed between the fluorine group of PVDF with oxygen-containing in the hydroxyl group of PVA. In-vitro cell culture showed that the enhanced hydrophilic property of electrospun PVDF/PVA could significantly enhance the cell growth. These positive results indicated that the scaffold could be implemented as artificial tissue material for tissue engineering applications.